Sistem Manajemen dan Biaya K3 Bangunan Gedung LP3M Unesa - Putra, Alwan Gangsar Brilian; Haq , Yusfira Afrianti (Menara: Jurnal Teknik Sipil, 2024)
The implementation of the Construction Occupational Health and Safety Management System (COHSMS) through the Occupational Health and Safety Contract Plan (OHS) aims to improve building quality and worker safety. Occupational Health and Safety Contract Plan (OHS) serves as a safety guideline in the execution of upper structure work in the Project for Constructing the Learning Development and Quality Assurance Institute Building at the State University of Surabaya. This study designs an Occupational Health and Safety Contract Plan (OHS) specifically for upper structure work in the aforementioned project. The hazard identification, risk assessment, and risk con,trol processes in the safety planning are conducted using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method in accordance with Ministry of Public Works Regulation No. 05 of 2014. This study analyzes hazard identification using the HIRARC method and calculates the costs incurred in the project. The results of this study can serve as an example for enhancing attention and implementation of health and safety practices in superstructure work for future projects, in accordance with good building planning standards.